Al Lawāsiq Fil Af’āl Ar Rubā’iyyah - Muhammad Taufiq Fadhlurrahman (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
AbstractThe word in Arabic has a free meaning if it has not been affixed to any letter, if there are affixes in it then it becomes bound, and changes its shape, and becomes narrower in meaning. This statement can be seen in the following example: "qarfaṣa" means sitting on the ground and holding hands under the feet, whereas if in the letter "ta" it becomes "taqarfaṣa" which means covering himself with clothes, and the word "za" 'za "a "which means to shake, when it ends with the letter" ta "then it becomes" za'za'at "which means she has been shaken. From the two previous examples, the researcher saw that the letter "ta" can change meaning and also narrow the meaning. Both are part of affixes in the ruba'i verb, so this paper will explain the type of affix in the ruba'i verb.Keywords: affix, ruba'i verb, meaning, enrollment. اللواصق في الأفعال الرباعية محمد توفيق فضل الرحمانجامعة دار السلام كونتورMtaufiq685@gmail.com ملخصإن الكلمات العربية لها معنى حر إذا لم تكن مرفقة بأي حرف، و إذا التحقت بالحرف فتصبح ملزمة وتغيرت شكلها وأضيق لها المعنى. تحقيقا لهذا البيان، يمكن أن نلاحظ هذه الكلمة "قرفص" التى لها المعنى "جلس على الأرض شادّاً يديه تحت رجليه", و التحق بحرف "التاء" فى أولها تكون"تقرفص" التى معنها "تلفف فى الثوب". الكملة "زعزع" لها المعنى "حركه بشدة"، و إذا اتصلت بالتاء تدل على ضمير بارز متصل تقدره هي فى أخرها وتكن "زعزعت" ، فمعنى يتغير إلى "هي متحركة بشدة". فمن هذان مثالان تبـــــــــــين أن الحرف "التاء" يفيد المعنى ويمكن تغيــير المعنى وتضييقه.  كل الحرف "التاء" في المثال هما من اللواصق التحقا بالكلمة الرباعية من الفعل. فسوف تشرح و تبين هذه الورقة أنواع اللصقة فى الفعل الرباعي.الكلمات المفتاحية: اللواصق، الفعل الرباعي، المعنى، الالتحاق.